A Chinese mission for Macau: to build bridges between China and the Portuguese Speaking Countries - Costa, C. M. (The Presence of China and the Chinese Diaspora in Portugal and Portuguese-Speaking Territories, 2020)
The handover of Macao in 1999, from Portugal to China, changed the political landscape of the territory forever. After five hundred years of Portuguese administration, the enclave joined the People’s Republic of China under the regime of ‘one country, two systems’. Since then, the Chinese central government opened the gaming industry to foreign investment, which has resulted in a very high economic performance. At the same time, Beijing gave Macao a task: to maintain the historical connections to the Lusophone world, which has contributed to the strengthening of relations not only with the Portuguese-speaking countries, but also to deepening ties with Africa and Latin America in general. Twenty years after the handover, Macao is expected to have reached a comfortable phase in achieving the goal of deepening relations with these countries, which raises some questions: Did the creation of Forum Macao significantly reinforce the role of Macao as a platform for Portuguese-speaking countries? Has Forum Macao contributed to bilateral and multilateral approaches between China and Portuguese-speaking countries? Is there a specific Chinese discourse for Portuguese-speaking countries, delivered through Forum Macao? In this chapter, we analyze Macao’s dynamics over the last two decades, and the official political discourse promoted by Forum Macao, in order to look for evidence of the deepening relationship between China and Portuguese-speaking countries.